حواضر وأعلام البناء الحضاري بالمغرب الأوسط - حناي, محمد; مياطه, التجاني (جامعة الوادي - University of Eloued, 2023)
بلاد المغرب الأوسط قاعدة ارتكاز لفتح الأندلس سنة 92ه/711م، لما كانت تزخر به من رجال أشاوس (الأمازيغ) اعتنقوا الإسلام وحملوا رسالته. هذا البعد الرِّسالي جعلها تحتضن فيما بعد العناصر الوافدة من المشرق الإسلامي، والتي تمازجت وتعايشت مع العنصر الأمازيغي واستطاعت أنْ تؤسس مع أخوة العقيدة الوافدين أوَّلُ دولة إسلاميَّة ببلاد المغرب الأوسط ألاَ وهي الدَّولة الرُّستميَّة (160/299ه – 776/911م)، التي كانت عاصمتها حاضرة "تيهرت" ذات الموقع الجغرافي الحصين والقابل للحياة والازدهار فيما هو آتٍ من أيام؛ وقد بلغت يومئذ شأناً عظيما في المدنيَّة والعمران حتى قورنت في ذاك الزَّمن بــ"قرطبة" و"بغداد" و"دمشق" وغيرها من عواصم المشرق الإسلامي، فكانت تُدعى بـــِ"عِراق المغرب"، وكذالك "بلخ المغرب". لقد زخرت هذه الحاضر الإسلامية ببلاد المغرب الأوسط بعلماء وأدباء تأثروا وأثروا في البناء الحضاري الإسلامي، ومن بينهم: "أبي الفضل أحمد التِّيهرتي"، و"بكر بن حماد" الشَّاعر، و "يهوذا بن قريش التِّيهرتي" في القرن 4ه، الذي كان متضلعاً في اللغات العبرانيَّة و الأرميَّة والفارسيَّة نهيك عن اللغة العربيَّة، مقدماً بعداً إثرائياً في علوم اللغات من خلال المقارنات، كما أنَّه هو الواضع لأسس النَّحو التَّنظيري؛ وهو ما يدلل على قيمة "تيهرت" وبنيتها العلميَّة الثَّقافية كحاضنة للعلم والعلماء. هذا الزَّخم الحضاري في دائرة التَّأثير والتَّأثر بقي متواصلاً ومستمراً في المحيطين القريب والبعيد من خلال أعلام هاته الحاضرة العاصمة الزَّاخرة بالمعصومة، ومثالنا على ذلك أنمودج دراستنا الشَّيخ "الحسن بن علي التِّهرتي" (5ه)، الذي تخرج على يد أئمة الأندلس متأثراً بهم وبمنهجهم، فكان أديباً نحوياً ومحدِّثاً فقيهاً موسوعياً، فأثر في كثير من علماء "المغرب" و "الأندلس" منهم "أبو الفضل القاضي عياض" صاحب المصنفات الشَّهيرة. بهذا الدَّور البنائي عاشت حاضرة "تيهرت" وأعلامها في دائرة الرِّساليَّة الإسلاميَّة تبني وتُشيِّد وتُقدم الرُّموز العلميَّة الواحد تلوى الأخر منذ تأسيسها وحتى بعد سقوط الدَّولة الرُّستميًّة، فقيمة المكان والزَّمان وغياب الحاكم العادل والنِّظام لا تلغي إنجاب الأعلام. The countries of the Central Maghreb are a base for the conquest of Andalusia in the year 92 AH / 711 CE, when it was full of Bravemen (Berbers) men who converted to Islam and carried their message. This missionary dimension made it embrace the incoming elements from the Islamic East, which blended and coexisted with the Amazigh element and was able to establish with the brotherhood of the arriving faith the first Islamic state in the countries of the Central Maghreb, which is the Al-Rostamiya state (160/299 AH - 776/911 AD), which was its capital. The "geothermal" location of the fortified, viable, and prosperous geography in the days to come. At that time, it reached a great affair in civilization and urbanism until it was compared in that time to "Cordoba", "Baghdad", "Damascus" and other capitals of the Islamic East, so it was called " "Iraq of Morocco", as well as "Balkh Morocco". This Islamic present in the countries of the Maghreb abounded with scholars and writers who were influenced and influenced in the Islamic civilizational structure, among them: “Abu al-Fadl Ahmad al-Tihriti”, “Bakr bin Hammad” the poet, and “Judah bin Quraysh al-Tihriti” in the 4th century AH, who was involved in The Hebrew, Armenian and Persian languages prohibit the Arabic language, providing an enriching dimension in the language sciences through comparisons, as it is the one setting the foundations for theoretical grammar, which indicates the value of "Tehert" and its cultural scientific structure as an incubator for science and scholars. This civilizational momentum in the circle of influence and influence has been continuous and continuous in the near and distant surroundings through the flags of this present capital, full of infallibility, and our example is the model of our study, Sheikh Al-Hassan bin Ali Al-Tahriti (5 AH), who came out at the hands of the imams of Andalusia affected by them and their approach. Grammarian and modern, an encyclopedic jurist, he influenced many scholars of "Morocco" and "Andalus", including "Abu al-Fadl al-Qadi Ayyad," the author of famous works. In this constructive role, the "Tihart" present and its flags in the Islamic missionary circle lived, constructed, constructed and presented the scientific symbols one after the other from its foundation until after the fall of the official state, the value of space and time and the absence of a just ruler and the system do not nullify the production of flags.
"تيهرت والحسن بن علي التِّيهرتي" أنموذجاً
مقال
Keywords: تيهرت - البناء الحضاري - المغرب الأوسط - الحسن بن علي التِّهرتي - الرِّساليَّة الإسلاميَّة; Tihart - civilizational construction - the Maghreb - Hassan ibn Ali alTahriti - Islamic missionary.